Engineered biological neuronal networks as basic logic operators - Küchler, Joël; Vulić, Katarina; Yao, Haotian; Valmaggia, Christian; Ihle, Stephan J.; Weaver, Sean; Vörös, János (Frontiers in Computational Neuroscience, 2025)
We present an in vitro neuronal network with controlled topology capable of performing basic Boolean computations, such as NAND and OR. Neurons cultured within polydimethylsiloxane (PDMS) microstructures on high-density microelectrode arrays (HD-MEAs) enable precise interaction through extracellular voltage stimulation and spiking activity recording. The architecture of our system allows for creating non-linear functions with two inputs and one output. Additionally, we analyze various encoding schemes, comparing the limitations of rate coding with the potential advantages of spike-timing-based coding strategies. This work contributes to the advancement of hybrid intelligence and biocomputing by offering insights into neural information encoding and decoding with the potential to create fully biological computational systems.